Mechanisms of environmental policy change in a federal system: The case of open federalism and the 2006–15 Harper government. Issue 2 (15th March 2018) - Wellstead, Adam M.
ABSTRACT: Between 2006 and 2011, the Canadian Conservative government advocated the concept of 'open federalism' which sought to minimize the role of the federal government in areas falling under provincial jurisdiction. Environmental policy-making was particularly impacted with the passage of the highly contentious 2012 omnibus Jobs, Growth and Long-term Prosperity Act, commonly known as Bill C-38. This paper argues that environmental policy needs to 'bring back federalism' into their analysis. In order to do so, a mechanisms approach is employed and focuses on the role of both macro and meso level historical institutionalism mechanisms in explaining policy layering and policy dismantling during this period.